Sex-related differences in the gastrointestinal disposition of ivermectin in the rat: P-glycoprotein involvement and itraconazole modulation - Lifschitz, Adrian Luis (2006)
Ivermectin (IVM), a macrocyclic lactone used as antiparasite agent, has been reported as a P‐glycoprotein (P‐gp) substrate. The participation of P‐gp in the IVM excretion process has been previously demonstrated. Sex‐related differences in the kinetic behaviour of some macrocyclic lactone compounds have been observed. The aim of this work was to characterize in‐vivo the comparative gastrointestinal disposition of IVM in male and female rats. The sex‐related influence on the itraconazole (ITZ) modulation of P‐gp‐mediated IVM intestinal transport was also assessed. Sixty Wistar rats (30 male, 30 female) received IVM alone or co‐administered with ITZ. Rats were killed between 6 and 72h after treatment and blood, gastrointestinal tissues and lumen contents were collected. IVM concentrations were determined by high performance liquid chromatography. Substantial sex‐related differences in the IVM disposition kinetics were observed. Higher IVM systemic availability was observed in female rats. The ITZ‐mediated modulation of the IVM disposition kinetics had a differential impact between male and female rats. Co‐administration with ITZ resulted in a marked increase in the IVM concentrations in the wall tissue from different portions of the gastrointestinal tract of male rats. The presence of ITZ induced drastic sex‐related changes on the P‐gp‐mediated IVM gastrointestinal disposition.